Left paratesticular mass mimicking polyorchidism: A case report - Ali, Nawaz; Kumar Singh, Khwairakpam Amit (Indian Journal of Case Reports, 2024)
We report a rare case of primary scrotal lipoma in a 20-year-old patient which clinically mimics a left triorchidism. The patients presented with the left testicular swelling and the ultrasonography of the scrotum revealed an inhomogeneous hyperechoic mass with an inconclusive report. The left scrotal hemi exploration was planned, and intraoperatively, it was found to be a paratesticular mass with an equivalent size corresponding to the left testicle, separate from the left testicle. The histopathology confirms the lipomatous swelling. The post-operative period remains uneventful and the patient has been on follow-up for the past 1 year with no relapse.